Experimental Acoustic Flow Analysis Inside a Section of an Acoustic Waveguide - Stefan WEYNA; Witold MICKIEWICZ; Michał PYŁA; Michał JABŁOŃSKI (Archives of Acoustics, 2013)
Noise propagation within ducts is of practical concern in many areas of industrial processes where a fluid has to be transported in piping systems. The paper presents experimental data and visualization of flow in the vicinity of an abrupt change in cross-section of a circular duct and on obstacles inside where the acoustic wave generates nonlinear separated flow and vortex fields. For noise produced by flow wave of low Mach number, laminar and turbulent flows are studied us- ing experimental sound intensity (SI) and laser particle image velocimetry (PIV) technique adopted to acoustics (A-PIV). The emphasis is put on the development and application of these methods for better understanding of noise generation inside the acoustic ducts with different cross-sections. The intensity distribution inside duct is produced by the action of the sum of modal pressures on the sum of modal particle velocities. However, acoustic field is extremely complicated because pressures in non-propagating (cut-off) modes cooperate with particle velocities in propagating modes, and vice versa. The discrete frequency sound is strongly influenced by the transmission of higher order modes in the duct. By under- standing the mechanism of energy in the sound channels and pipes we can find the best solution to noise abatement technology. In the paper, numerous methods of visualization illustrate the vortex flow as an acoustic velocity or sound intensity stream which can be presented graphically. Diffraction and scattering phenomena occurring inside and around the open-end of the acoustic duct are shown.